High-redshift, Small-scale Tests of Ultralight Axion Dark Matter Using Hubble and Webb Galaxy UV Luminosities - Harrison Winch; Keir K. Rogers; Renée Hložek; David J. E. Marsh (The Astrophysical Journal, 2024)
We calculate the abundance of UV-bright galaxies in the presence of ultralight axion (ULA) dark matter (DM), finding that axions suppress their formation with a non-trivial dependence on redshift and luminosity. We set limits on axion DM using UV luminosity function (UVLF) data, excluding a single axion as all the DM for m _ax < 10 ^−21.6 eV and limiting axions with $-26\leqslant \mathrm{log}({m}_{{\rm{ax}}}/\mathrm{eV})\leqslant -23$ to be less than 22% of the DM (both at 95% credibility). These limits use UVLF measurements from 24,000 sources from the Hubble Space Telescope (HST) at redshifts 4 ≤ z ≤ 10. We marginalize over a parametric model connecting halo mass and UV luminosity. Our results bridge a window in axion mass and fraction previously unconstrained by cosmological data, between large-scale cosmic microwave background and galaxy clustering and the small-scale Ly α forest. These high- z measurements provide a powerful consistency check of low- z tests of axion DM, including the recent hint for a sub-dominant ULA DM fraction in Ly α forest data. We also consider a sample of 25 spectroscopically confirmed high- z galaxies from the James Webb Space Telescope (JWST), finding these data to be consistent with HST. Combining HST and JWST UVLF data does not improve our constraints beyond HST alone, but future JWST measurements have the potential to improve these results. We also find an excess of low-mass halos (<10 ^9 M _⊙ ) at z < 3, which could be probed by subgalactic structure probes (e.g., stellar streams, satellite galaxies, and strong lensing).